Investigating consumer perceptions of fairness in financial services - Rahul, Bhatia (2009)
Purpose – The purpose of this dissertation is to investigate consumer perceptions of fairness in financial services. Design/Methodology/approach – The research involved a review of available literature on financial service industry, fairness issue, the identification of factors that affects consumer behaviour and articles on Indian and UK consumer’s experiences with different financial service providers. A research questionnaire was administered with the help of internet surveys to 50 consumers each in India and United Kingdom. Findings – Indian consumers are more satisfied with the financial service providers as compared to UK consumers. Present scenario of UK financial service market: The Banks and financial institutions are not putting consumers first. They are not providing them quality products and services. They are just treating them fairly for their own sake and to stay for a longer period of time in the market. In the case of India, though financial service providers such as banks etc are lacking in few aspects but overall Indian consumers are happy with the way the banks and financial institutions are providing them services. Research limitations/implications – Limitations relate to the use of small sample size and the time restrictions associated with the research study. This study contributes to the body of academic knowledge by shedding more light into the consumer perception of fairness in the financial services. Key words – Financial services, Financial products and services, Fairness, Consumer behaviour, Consumer perceptions, Banks, India, United Kingdom.